Autophagic Inhibition of Caveolin-1 by Compound Phyllanthus urinaria L. Activates Ubiquitination and Proteasome Degradation of β-catenin to Suppress Metastasis of Hepatitis B-Associated Hepatocellular Carcinoma - Huang, Danping; Yang, Bowen; Yao, Yaoyao; Liao, Mianmian; Zhang, Yu; Zeng, Yihao; Zhang, Fengxue; Wang, Neng; Tong, Guangdong (Frontiers in Pharmacology, 2021)
Compound Phyllanthus urinaria L. (CP) is a traditional Chinese medicine (TCM) formula for cancer treatment in the clinic, particularly during progression of hepatitis B-associated hepatocellular carcinoma (HBV-associated HCC). Nevertheless, its anti-metastatic action and mechanisms are not well elucidated. In this study, CP was found to exert remarkable inhibitory effects on the proliferation, migration and invasion of HBV-associated HCC cells. The following network and biological analyses predicted that CP mainly targeted Caveolin-1 (Cav-1) to induce anti-metastatic effects, and Wnt/β-catenin pathway was one of the core mechanisms of CP action against HBV-associated HCC. Further experimental validation implied that Cav-1 overexpression promoted metastasis of HBV-associated HCC by stabilizing β-catenin, while CP administration induced autophagic degradation of Cav-1, activated the Akt/GSK3β-mediated proteasome degradation of β-catenin via ubiquitination activation, and subsequently attenuated the metastasis-promoting effect of Cav-1. In addition, the anti-cancer and anti-metastatic action of CP was further confirmed by in vivo and ex vivo experiments. It was found that CP inhibited the tumor growth and metastasis of HBV-associated HCC in both mice liver cancer xenograft and zebrafish xenotransplantation models. Taken together, our study not only highlights the novel function of CP formula in suppressing metastasis of HBV-associated HCC, but it also addresses the critical role of Cav-1 in mediating Akt/GSK3β/β-catenin axis to control the late-phase of cancer progression.